Discrepancy in Educational Materials between Higher Education Institutions and the Requirements of the Professional Workforce in the Job Market - Dewi, Rahmatika (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
The rise of ICT specialists in the computer field due to Industry 4.0 is notable, particularly in Indonesia's e-commerce and technology-driven markets. This study explores the demand for qualified informatics engineering professionals, focusing on their ICT and English language skills. Employing a qualitative phenomenological case study design, the research gathered data through semi-structured interviews with informatics engineering specialists and employers. It also scrutinized an English lesson program at a polytechnic in Indonesia through interviews with key figures and document analysis. The study identifies two key findings: demand emphasizes the critical role of reading skills, especially in programming languages and technology documentation, while supply reveals a gap between higher education materials and workplace requirements. The curriculum appears to neglect English proficiency, hindering graduates' performance. Consequently, the study advocates for higher education reform, urging institutions to align their programs with industry demands. Collaboration between government, universities, and industry stakeholders, especially at the regional level, is proposed to bridge the gap and enhance the preparedness of informatics engineering graduates for the evolving industry landscape. The findings underscore the importance of creativity and originality in technology creation, urging institutions to adapt swiftly to the dynamic informatics engineering landscape.